Diving Medicine - Rusoke-Dierich, Olaf (Springer International Publishing, 2018)
This book is the very first to cover the decompression theory in detail. It gives many information on all topics of the diving medicine, and is richly and uniquely illustrated. It offers a good guideline of high quality practice in diving medicine. The author provides a very structured and easy to understand book, by covering all aspects of the diving medicine, such as equipment, physiology, and related issues as gas intoxications, venomous animals or damages that can occur in the diving practice. Relevant physiological and anatomical illustrations enlight even complex topics. The Diving medicine book will appeal to health experts like doctors and nurses, but also to diving schools and teachers.